Design and Simulation of variable gain amplifier using cadence Tool - Penchalaiah, Dr. Usthulamuri; Vamsi, Devandla; Siddardha, Aata; Reddy, Banka Pavan Kumar; Gnaneswar, Bachu (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
The radio frequency (RF) amplifiers are widely used in a variety of communication systems. However, the conventional analog RF resulted in reduced volage gain, magnitude, and phase responses. So, this work provides an overview of a research paper focused on the design and analysis of a single-stage variable gain amplifier (SSVGA) utilizing cascaded linear transconductance amplifier (Gm cell) and linear transimpedance amplifier (TIA) blocks with feedback via shunt resistors. The SSVGA architecture aims to maintain constant bandwidth while offering controllable voltage gain, making it versatile for applications with varying input signal strengths. The first stage of the SSVGA is realized as a current mode TIA, converting the input voltage signal to an output current efficiently. The second stage features a Gm cell with source degeneration, enhancing bias current efficiency and transconductance at the supply voltage. The proposed SSVGA design offers flexibility and adaptability, making it suitable for diverse communication systems and signal processing applications. The incorporation of feedback control ensures consistent performance across different voltage gain settings, resulting in a robust and efficient solution for varying signal strengths.